Cortical lesions impact cognitive decline in multiple sclerosis via volume loss of nonlesional cortex - Eva A. Krijnen; Maureen vanDam; Albulena Bajrami; Piet M. Bouman; Samantha Noteboom; Frederik Barkhof; Bernard M.J. Uitdehaag; Martijn D. Steenwijk; Eric C. Klawiter; Ismail Koubiyr; Menno M. Schoonheim (Annals of Clinical and Translational Neurology)
Abstract Objective To assess the interrelationship between cortical lesions and cortical thinning and volume loss in people with multiple sclerosis within cortical networks, and how this relates to future cognition. Methods In this longitudinal study, 230 people with multiple sclerosis and 60 healthy controls underwent 3 Tesla MRI at baseline and neuropsychological assessment at baseline and 5‐year follow‐up. Cortical regions (N = 212) were divided into seven functional networks. Regions were defined as either lesional or normal‐appearing cortex based on presence of a cortical lesion on artificial intelligence‐generated double inversion‐recovery scans. Cortical volume and thickness were determined within lesional or normal‐appearing cortex. Results Prevalence of at least one cortical lesion was highest in the limbic (73%) followed by the default mode network (70.9%). Multiple sclerosis‐related cortical thinning was more pronounced in lesional (mean Z‐score = 0.70 ± 0.84) compared to normal‐appearing cortex (−0.45 ± 0.60; P < 0.001) in all, except sensorimotor, networks. Cognitive dysfunction, particularly of verbal memory, visuospatial memory, and inhibition, at follow‐up was best predicted by baseline network volume of normal‐appearing cortex of the default mode network [B (95% CI) = 0.31 (0.18; 0.43), P < 0.001]. Mediation analysis showed that the effect of cortical lesions on future cognition was mediated by volume loss of the normal‐appearing instead of lesional cortex, independent of white matter lesion volume. Interpretation Multiple sclerosis‐related cortical thinning was worse in lesional compared to normal‐appearing cortex, while volume loss of normal‐appearing cortex was most predictive of subsequent cognitive decline, particularly in the default mode network. Mediation analyses indicate that cortical lesions impact cognitive decline plausibly by inducing atrophy, rather than through a direct effect.